2015
DOI: 10.1007/s11356-015-5576-2
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of benzo(a)pyrene by two freshwater microalgae Selenastrum capricornutum and Scenedesmus acutus: a comparative study useful for bioremediation

Abstract: A comparative evaluation of the removal of benzo(a)pyrene (BaP) by sorption and degradation by two microalgal species, Selenastrum capricornutum and Scenedesmus acutus was performed. The monitoring of the amount of BaP remaining in the liquid culture media and the biomass along with the appearance of three metabolites (4,5 dihydrodiol-BaP; 7,8-dihydrodiol-BaP; and 9,10 dihydrodiol-BaP) at short time periods (from 0.25 to 72 h) in cultures exposed to BaP was made by high-performance liquid chromatography (HPLC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…In another study, the efficiency of seven microalgal species to remove pyrene from solution was reported (Lei et al, 2002). In a recent study removal of benzo(a)pyrene (BaP) by sorption and degradation was determined by two microalgal species Selenastrum capricornutum and Scenedesmus acutus (Garcia de Llasera et al, 2016). It has been seen that S. capricornutum can remove 99% of BaP after 15 h of exposure, whereas S. acutus can remove 95% after 72 h of exposure.…”
Section: Microalgal Degradation Of Pahsmentioning
confidence: 99%
“…In another study, the efficiency of seven microalgal species to remove pyrene from solution was reported (Lei et al, 2002). In a recent study removal of benzo(a)pyrene (BaP) by sorption and degradation was determined by two microalgal species Selenastrum capricornutum and Scenedesmus acutus (Garcia de Llasera et al, 2016). It has been seen that S. capricornutum can remove 99% of BaP after 15 h of exposure, whereas S. acutus can remove 95% after 72 h of exposure.…”
Section: Microalgal Degradation Of Pahsmentioning
confidence: 99%
“…PAH biodegradation employs both monooxygenase and dioxygenase enzymatic pathways and produces hydroxylated and dihydroxylated intermediates, respectively, depending on the algal type ( Chan et al, 2006 ). Microalgae (Cyanobacteria) are freshwater unicellular green alga, have gained huge attention for its ubiquitous occurrence, easy to propagate, and most prominent efficiency of degrading HMW PAHs ( Ke et al, 2010 ; De Llasera et al, 2016 ). Few reports on alga-based PAH bioremediation are listed in Table 2 .…”
Section: Bioremediation Of Polycyclic Aromatic Hydrocarbon Pollutantsmentioning
confidence: 99%
“…This is because cyanobacteria or microalgae release a variety of light weight compounds and extrapolymeric compounds composed of nucleic acids, lipids, proteins, excretion products and fermentation products that serve as microbial growth substrates which, in turn, enhance the degradation potential of aliphatic and aromatic contaminants by the bacteria (Kirkwood et al, 2006). Also, microalgae supply oxygen for enhancing aerobic degradation of contaminants (de Llasera et al, 2016).…”
Section: Mixed Cell Culture Systemmentioning
confidence: 99%